Can invasive alien fish species act as effective hosts of native freshwater mussels (Unionidae) in Iberia? - Teixeira, Amílcar (2018)
The freshwater biodiversity of Mediterranean areas is severely threatened by several human activities, including habitat loss and fragmentation, river regulation, pollution, overexploitation, climate change and introduction of invasive alien species (IAS). These human disturbances drastically affect native fish and mussel populations and possibly conservation measures are needed to implement to revert major problems. Particularly at risk may be affiliate species such as freshwater mussels (Bivalvia, Unionoida) that have an obligatory parasitic phase of a short-term larval stage on fish host gills and fins. In Iberia, the identification of effective fish hosts for unionid species and the impact of IAS remain unclear. In this study, field and laboratorial studies were performed to assess the fish hosts for Anodonta anatina, Unio delphinus and Potomida littoralis. For in situ monitoring done in Douro basin (Northern Portugal), results showed an effective infestation for native (Luciobarbus bocagei, Squalius carolitertii, Squalius alburnoides and Pseudochondrostoma duriense) but also for non-native (Lepomis gibbosus, Alburnus alburnus, Gambusia holbrooki and Gobio lozanoi) fishes. The highest infestation rate and prevalence were observed for L. bocagei and S. carolitertii, but also for L. gibbosus. However, in laboratorial experiments significant differences were found. In fact, for U. delphinus and P. littoralis only native fishes (mainly endemic cyprinids) showed to be effective hosts, since viable juveniles were produced. A. anatina exhibited a more generalist behavior, with a wide range of native (endemic cyprinids of north and south Iberia) and non-native (Australoheros facetus, Oncorhynchus mykiss, Esox lucius, Phoxinus phoxinus, A. alburnus and G. lozanoi) fish host species. Overall, our results showed: 1) the importance of native fish species for the maintenance of a good conservation status of native unionids; 2) some invasive fish species can also function as hosts of A. anatina and 3) basic ecological data using field monitoring and laboratorial experiments are fundamental to design future conservation measures such as reproduction in captivity and propagation of threatened unionids.